STUDI PETROGRAFI BATUPASIR FORMASI WALAT DAERAH CIBADAK, SUKABUMI: IMPLIKASINYA TERHADAP TIPE PROVENAN - Ismiyati (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2021)
The Walat Formation is an Paleogen siliciclastic sedimentary rock formed in the Bogor Basin. Outcrops of this formation are widespread in the Cibadak area such as in Gunung Walat, the Sand Bongkok Complex, Aseupan Sand, and the Cicareuh River. Several studies have been done before on this formation. However, studies on provenance with petrographic methods are still rarely conducted, especially in the research area. This is the basis of this study. The data used in this study consisted of field data and previous research literature. The location of field data collection is located in the south of Gunung Walat, precisely in the Holcim Educational Forest (HEF) using the measured stratigraphic method. A total of 18 sandstone samples were using the petrographic. From one existing track, three facies were identified, namely Sp (planar-cross-bedded sand), Gh (clast supported, horizontally stratified gravel), and Fl (laminated sand, silt, and mud). This facies distribution is based on lithology, grain size, and sedimentary structure. Petrographic data indicate that the sandstones of the Walat Formation are mostly lithic arenite, sublithic arenite, and lithic-graywacke. Comparison of QFL composition shows that all sandstones come from orogenic deposits with Q compositions (78.51% - 97.74%), F (0 - 1%), and L (2.26% - 21.13%) meanwhile, QmFLt comparisons show originating from quartz recycled (three samples), transitional recycled (11 samples), and lithic recycled (four samples).